2013
DOI: 10.1016/j.bpj.2013.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Titratable Water to All-Atom Molecular Dynamics at Constant pH

Abstract: Recent development of titratable coions has paved the way for realizing all-atom molecular dynamics at constant pH. To further improve physical realism, here we describe a technique in which proton titration of the solute is directly coupled to the interconversion between water and hydroxide or hydronium. We test the new method in replica-exchange continuous constant pH molecular dynamics simulations of three proteins, HP36, BBL, and HEWL. The calculated pKa values based on 10-ns sampling per replica have the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
160
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(167 citation statements)
references
References 12 publications
7
160
0
Order By: Relevance
“…Surprisingly, despite all approximations, predicted pK a values obtained by the FPTS are in general at least within the range of values given by different theoretical models (Stanton and Houk 2008;Chen et al 2013;Barroso da Silva and MacKernan 2017b). A recent benchmark study demonstrated that in fact even atomistic-level molecular dynamics simulations at constant pH do not obtain better results than FPTS for some protein systems.…”
Section: Titration Schemes Based On the Monte Carlo Methodsmentioning
confidence: 69%
See 3 more Smart Citations
“…Surprisingly, despite all approximations, predicted pK a values obtained by the FPTS are in general at least within the range of values given by different theoretical models (Stanton and Houk 2008;Chen et al 2013;Barroso da Silva and MacKernan 2017b). A recent benchmark study demonstrated that in fact even atomistic-level molecular dynamics simulations at constant pH do not obtain better results than FPTS for some protein systems.…”
Section: Titration Schemes Based On the Monte Carlo Methodsmentioning
confidence: 69%
“…This was the beginning of a new era of CpH simulation methods still under intense development for biological systems (Baptista et al 1997;Wallace and Shen 2012;Dashti et al 2012;Goh et al 2013a;Chen et al 2013Chen et al , 2014Chen and Roux 2015;Socher and Stich 2016;Donnini et al 2016). Several new simulation schemes that allow pH-coupled MD have emerged following either the Baptista's hybrid MD/PB approach (Baptista et al 1997) or are rooted in the "λ"'s dynamics method (Kong and Brooks 1996).…”
Section: Other Common Constant Ph Simulation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Most recently, an all-atom CpHMD method was developed, which uses explicit solvent to drive the dynamics in both conformational and protonation states, thus enabling the effects of ions to be explicitly taken into account. 18 Furthermore, titratable co-ions 18 or water molecules 19 are included in the simulation system to ensure charge neutrality under all pH conditions and at all time. Here we apply the all-atom CpHMD with titratable water to reexamine the titration of lauric acid in the DTA micelle.…”
Section: Introductionmentioning
confidence: 99%